PENGARUH KUALITAS PELAYANAN PEMBUATAN KARTU KELUARGA (KK) TERHADAP KEPUASAN MASYARAKAT PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL - Rahayu Oktian Siregar; Tuah Nur; Dine Meigawati (LPPM Universitas Djuanda Bogor, 2023)
Customer satisfaction is a crucial aspect that is influenced by the quality of service provided. Institutions that offer public services are obligated to deliver efficient, effective, and high-quality services that meet the needs of the public. This requires optimizing all available resources, such as infrastructure, personnel, facilities, and technological systems. However, initial observations suggest that the Family Card service provided by the Department of Population and Civil Registration in Sukabumi Regency does not adhere to the one-day service procedure due to inadequate service officers and impolite staff. The objective of this study is to investigate the correlation between service quality and customer satisfaction using a quantitative method with a descriptive and associative approach. A sample of 100 family card applicants was selected using accidental sampling at the department. The data analysis involved using simple linear regression analysis, including a coefficient of determination test, simple correlation coefficient, and partial test (T-test). The study's results indicate that there is a link between service quality and customer satisfaction.